Patent cultures : diversity and harmonization in historical perspective / edited by Graeme Gooday, Steven Wilf. - Gooday, Graeme, 1965-; Wilf, Steven Robert (Cambridge intellectual property and information law ;, 2020)
This book explores how dissimilar patent systems remain distinctive despite international efforts towards harmonization. The dominant historical account describes harmonization as ever-growing, with familiar milestones such as the Paris Convention (1883), the World Intellectual Property Organization's founding (1967), and the formation of current global institutions of patent governance. Yet throughout the modern period, countries fashioned their own mechanisms for fostering technological invention. Notwithstanding the harmonization project, diversity in patent cultures remains stubbornly persistent. No single comprehensive volume describes the comparative historical development of patent practices. Patent Cultures: Diversity and Harmonization in Historical Perspective seeks to fill this gap. Tracing national patenting from imperial expansion in the early nineteenth century to our time, this work asks fundamental questions about the limits of globalization, innovation's cultural dimension, and how historical context shapes patent policy. It is essential reading for anyone seeking to understand the contested role of patents in the modern world.